QUALIFYING AND QUANTIFYING THE INTANGIBLE FACTORS THAT ENHANCE IN INFRASTRUCTURE ASSET VALUATION - Hamzah, Ezdihar; Mohd Rohaizad, Nur Farah Hanna; Abdullah Hashim, Hariati; Ismail, Azizah (PLANNING MALAYSIA, 2022)
Infrastructure asset are included as a special property when one is conducting a valuation. The uniqueness of an infrastructure asset due to its specific functions and operations that are differ from other infrastructure asset. Thus, the tangible and intangible factors included for valuation are also difference and specialize according to each infrastructure asset. The issues of intangible factors that enhance in infrastructure asset valuation are arisen since the investor and stakeholders are concern in getting to know how much the asset are generating a profit compare to its expenses in operating the asset especially a public asset. This research aims to evaluate the application of intangible factors in infrastructure asset valuation. As intangible factors are unforeseen factors, thus this research elaborates on detailed intangible factors and how to identify the factors that influence to the value. The methodology adopted in this research is based on qualitative analysis by in depth interview with the experts that specialized in special property valuation. The research findings are derived from the content analysis. Based on the interview expert’s session, this paper has also benefit in the form of knowledge and to the practitioner in implementing the intangible factors in infrastructure asset valuation.